Determinant Efforts To Handle Temper Tantrum At Tazkia Islamic Kindergarten Students, Sunggal District, Deli Serdang Regency - Widya, Rika; Salma Rozana; Rustam Ependi; Zahrita (ASIAN PUBLISHER, 2024)
Temper tantrums will occur when children do not get what they want, feel frustrated, tired and hungry. Children at this age are still unable to express their feelings verbally well so they tend to use actions to express their feelings. Based on the results of observations at Tazkia Islamic Kindergarten, the researchers found that there were several children who experienced tantrums in the classroom during breaktime. This study used the literature study approach and a descriptive qualitative methodology using library research. It was found that factors that caused temper tantrum in children, they were parents’ education, family communication style, children’s emotional intelligence, and teachers’ effort to handle temper tantrum. At the stage of social emotional development in early childhood, parents and educators need to pay attention to children. Many times a child will experience temper tantrums as a mechanism to get attention. Therefore, the best advice a parent can give in this situation is to ignore the behavior until the child calms down and the tantrum goes away, as long as the child is not in danger or not harming others. Ignoring the behavior shows the child that acting out does not result in parental attention. However, if the child hits or kicks someone, parents should restrain the child until the behavior stops and the child calms down and not talk to the child until the child calms down.